A dynamic heterogeneous labour demand model for German manufacturing - Falk, Martin,Koebel, Bertrand M. (ZEW, 2000)
This paper presents an application of the Generalised Error Correction Model (GECM) for heterogeneous factor demands based on the quadratic cost function. Using data for 26 West German manufacturing industries over the period 1976-1995, it turns out that less general specifications such as the partial adjustment and the static AR(1) model are rejected. Furthermore, both shortrun and long-run labour demands of different skill classes are inelastic. Unskilled labour is found to have a somewhat higher wage elasticity in absolute terms than medium-skilled labour. A small part of shift in demand away from unskilled labour can be explained by the substitutability relationship between intermediate materials and unskilled labour. Between 6 and 13 percent of the observed shift towards high-skilled labour can be explained by capital accumulation.
Auch im Internet unter der Adresse ftp://ftp.zew.de/pub/zew-docs/dp/dp0016.pdf verfügbar
Keywords: Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Arbeitsnachfrage; Humankapital; Kostenfunktion; Dynamische Wirtschaftstheorie; Preiselastizität; Substitutionselastizität; Schätzung; Industrie; Deutschland; Kointegration